CINEMATIC REPRESENTATION OF ISLAMIC LEADERSHIP: A STUDY ON HADRATUS SHAYKH K.H. HASYIM ASY'ARI IN SANG KYAI - Mutrofin; Umi Nur Hanifah; Latif Amrullah (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2025)
This research examines and analyzes the role and character of a prominent Islamic scholar in Indonesia, Hadratus Syekh Kyai Haji Hasyim Asy'ari, as portrayed in the film Sang Kiai. K.H. Hasyim Asy'ari is a figure of great influence in the history of Islam in Indonesia, particularly as the founder of Nahdlatul Ulama (NU), the largest Islamic organization in the country. The film Sang Kiai depicts his life journey and leadership role in advocating for religion, justice, and national independence. Through the analysis of the leadership characteristics portrayed in the film, this research investigates the leadership concepts embodied by Hadratus Syekh KH Hasyim Asy'ari, including spiritual leadership, wisdom-based governance, justice, and compassion for the community. The findings provide in-depth insights into the role of leadership character and the leadership concepts of K.H. Hasyim Asy'ari as depicted in Sang Kiai, offering inspiration for contemporary leaders to lead with integrity, justice, empathy, and in accordance with Islamic principles. The methodology employed in this research is a qualitative method with narrative analysis, resulting in descriptive data.